(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Deciding whether a person is mafqud (missing and presumed dead) is very important to Muslims and non-Muslims as the process of distribution of the deceased’s estate will be difficult if it is unknown whether the person is still alive or dead. Accordingly, a person must be pronounced mafqud (presumed dead) by the court. It is the aim of this article to draw a comparison between the presumption of death from the perspective of civil and Syariah law in Malaysia. In addition, the article attempts to evaluate the current practice of both the civil and Syariah courts in dealing with the presumption of death. It appears there are variations in the period required for the establishment of the presumption of death in the civil and Syariah courts. Based on decided cases, Muslim heirs of al-mafqud have the option to apply to civil court or Syariah court to obtain a declaration of presumption of death. Keyword: Mafqud, missing person, presumption of death, civil court, Syariah court